THE EFFECT OF PERCEIVED VALUE AND BRAND EXPERIENCE ON CUSTOMER REPURCHASE INTENTION - Rambitan, Tasya Febriani (FEB Universitas Sam Ratulangi Manado, 2013)
The global competition nowadays, some companies base their business model where customers are placed above and avokasi customers have become their strategy and competitive advantage. But to get customers is not enough, companies tend to try to obtain or increase the customers attraction and create repurchase intention. The more purchase that come from the consumers and customers the more revenues company get. The research objective in this study to analyze, is there the influence of perceived value and brand experience on customer repurchase intention and how the influences of perceived value and brand experience on customer repurchase intention. Theories supporting research are: perceived value, brand experience, and repurchase intention. The population of this research is the people in Manado with sample of 60 respondents using accidental sampling. The conclusions are:(1) perceived value is the most significant than brand experience on repurchase intention, and (2) brand experience shown have an influence but not significant towards Repurchase Intention in Manado. In this research we found that perceived value is the importance factor to see how customer repurchase intention, people will consider to repurchase the products depend on perceived value of the products, while brand experience not significantly effect people to repurchase, people no need brand experience to make repurchase intention of this product, because cocacola has been the famous product in the world, people knew the product and they will buy or repurchase the product not depend on brand experience. Keywords: perceived value, brand experience, repurchase intention